2003
DOI: 10.1291/hypres.26.521
|View full text |Cite
|
Sign up to set email alerts
|

Salt Sensitivity of Japanese from the Viewpoint of Gene Polymorphism

Abstract: Excess salt intake is an important environmental risk for the predisposition to essential hypertension. Previous physiological studies have shown that salt sensitivity is associated with insulin resistance, enhancement of sympathetic nerve activity and decrease of blood pressure decline at night. We have been examining the genetic importance of candidate gene polymorphisms of salt-sensitive hypertension using several populations. The angiotensinogen gene (AGT ) is Key Words: genetics, non-dipper, insulin resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(116 citation statements)
references
References 25 publications
3
110
2
1
Order By: Relevance
“…In fact, as an ancestral gene 28 in RAAS, the angiotensinogen (AGT) gene has been considered as a thrifty gene. 28,[38][39][40] In the present study, we chose the ACE gene, another ancestral hypertension susceptibility gene in RAAS, to explore the evolutionary ecological evidence for the 'thrifty genotype' hypothesis within the framework of spatial genetics and spatial ecology.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, as an ancestral gene 28 in RAAS, the angiotensinogen (AGT) gene has been considered as a thrifty gene. 28,[38][39][40] In the present study, we chose the ACE gene, another ancestral hypertension susceptibility gene in RAAS, to explore the evolutionary ecological evidence for the 'thrifty genotype' hypothesis within the framework of spatial genetics and spatial ecology.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, van Rijn et al [69] found an association between the AGT TT genotype and atherosclerosis and white matter lesions (WML). In addition, the AGT 235T allele has been reported to contribute to salt sensitivity [70] . However, the effect of the AGT gene polymorphism on the risk of ischemic stroke remains controversial [71] .…”
Section: Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
“…What is known about this topic K Renin-angiotensin system polymorphisms are genetic determinants of essential hypertension and end-organ damage 12 K Renin-angiotensin system polymorphisms are associated with salt sensitivity, but the results obtained are controversial 3-5 K The polymorphism of the angiotensin II type 2 receptor (AGTR2) gene which is located on X chromosome is associated with hypertension 6,7 What this study adds K Significant linear increases in both systolic blood pressure and diastolic blood pressure are associated with increased salt intake in the subjects with the A genotype, but not in those with the C genotype of AGTR2 K Subjects with the A genotype of AGTR2 have a significantly higher risk for hypertension than those with the C genotype in the fourth quartile of daily sodium intake (the highest group), while the odds ratios in the first, second, and third quartiles were not significant…”
Section: Summary Of the Present Studymentioning
confidence: 99%
“…[3][4][5] With regard to the angiotensin II type 2 receptor (AGTR2) gene, some studies examined the relationship between AGTR2 gene polymorphisms and hypertension, 6,7 but there are no studies investigating the relationship between the polymorphisms and salt sensitivity to our knowledge.…”
mentioning
confidence: 99%